Describing of Ethnopedagogical Leadership Contribution to Towani Tolotang Community Based on Local Wisdom Values in Elementary Schools - Elihami Elihami (Universitas Muhammadiyah Enrekang, 2022)
The research objective is to know the dialectic of ethnopedagogical leadership on the trust of the Towani Tolotang community. The research method uses descriptive research. The data were collected using a questionnaire from a variable in the form of a discourse on the local wisdom of the Towani Tolotang community which is manifested in the concept of